RETROSPECTIVE EVALUATION OF WEIGHT LOSS TREATMENT IN OVERWEIGHT AND OBESE PERSONS WITH DIABETES IN CLINICS IN LAGOS, NIGERIA - Fasanmade, Olufemi; Odeniyi, Ifedayo; Olopade, Oluwarotimi; Fashola, Waliu (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVES Attainment of ideal weight in diabetes is vital. This retrospective study aims to evaluate how much weight patients were able to lose and the determinants of successful weight loss. METHODOLOGY Records of obese (BMI >30 kg/m2) type 2 patients of two clinics in Lagos (public and private) were retrieved and biodata and weight records were perused. Drugs used to ensure weight loss were also extracted. RESULTS We studied 152 patient records. Their mean height was 1.65 m and their mean weight was 108 kg (mean BMI of 39.7 kg/m2). Weight loss management included non-structured dietary counsel given to all the patients, 1-3 weight-reducing drugs including orlistat, topiramate, SGLT-2 inhibitors, and GLP-1RAs. The mean weight loss was 4.96 kg (range -30 to + 28 kg) for those managed with weight loss drugs. The weight loss in 108 (71.4%) was over a period of 1-3 years. Sustained weight loss of range 1-30 kg was observed with a mean weight loss of 12.4 kg in this group. The 28.6% who did not lose weight gained 1-28 kg, a mean weight gain of 4.16 kg over the same period. Those who experienced the greatest weight loss were on dual, triple, or quadruple therapy in addition to the diet. Only 3 patients had bariatric surgery for weight loss which was beneficial in one (lost 31 kg), equivocal in one (only transient weight loss and regained most of the weight), and not measurable in the 3rd (lost to follow-up). CONCLUSION Obese DM patients require active and aggressive combi- nation/multidisciplinary care for improved metabolic and obesity control.